Temperature And Speed Monitoring On Google Sheet-Based Motorcycle Discs - Wibowo, Akbar Ari; Syahrorini, Syamsudduha; Wisaksono, Arief (Information Technology and Science (ITScience), 2023)
The braking system for motor vehicles is very important which serves to slow down speed. So that the braking system is one that must be considered for driving safety. There are two types of braking systems on motorcycles based on the mechanism, namely braking using discs and drums. One of the causes of road accidents is because the brakes overheat so that failure of the braking system results in brake failure. Therefore, this research is about the design of temperature and speed monitoring on motorcycle brake discs based on google sheets. Which uses MLX90614 sensor as a temperature sensor and E18-D80NK sensor as a speed sensor and NodeMCU ESP8266 as a microcontroller. Both sensors are programmed to provide information so that the brake temperature does not overheat and turn on the buzzer when the temperature and speed reach / exceed predetermined values. The buzzer will turn on when the temperature on the disc brakes reaches ?65°C and when the speed reaches 120rpm.